PENGARUH METODE DISCOVERY LEARNING MENGGUNAKAN APLIKASI AUGMENTED REALITY (AR) TERHADAP PEMAHAMAN KONSEP IPA PESERTA DIDIKKELAS IV SD NEGERI NGERUKEMAN - Siti Nurfitri; Urip Muhayat Wiji Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Discovery Learning method based on the Augmented Reality (AR) application on the science concept understanding of fourth-grade elementary school students. In addition, this study also aims to examine the extent to which the method can improve students' conceptual understanding in science learning, which was previously low and tended to rely on memorization. This research employs a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest design. The subjects of this study were fourth-grade students of SD Negeri Ngerukeman. Data collection techniques were carried out through tests (pretest and posttest), while data analysis used normality tests, homogeneity tests, and hypothesis testing (Independent Sample T-Test). The results of the study indicate that the Discovery Learning method based on the Augmented Reality (AR) application has a significant effect on improving students' understanding of science concepts. This is evidenced by a significance value of 0.011 < 0.05 and a higher increase in the average score in the experimental class compared to the control class. Therefore, this method is proven to be effective in enhancing students’ conceptual understanding and in creating more interactive and meaningful learning experiences.